Exposición a aflatoxina : un problema de salud pública (2014)
ABSTRACT: Aflatoxin, a mycotoxin produced by pollutant molds, is a potent hepatotoxic and carcinogenic agent. Dietary exposition to it is of particular importance in certain regions of Southeast Asia and sub-Saharan Africa. Populations in these regions suffer from high incidence of hepatocellular carcinoma, and have high frequency of the mutation in the codon 249 of p53 gene; besides, prevalence of Hepatitis B virus (HBV) infection is high in those populations. Synergism between infection with HBV and the exposition to this mycotoxin in the pathogenesis of hepatocellular carcinoma has been demonstrated. Few studies have explored the exposition to aflatoxin in the diet of populations in Latin America, and the role in them of this mycotoxin as a risk factor for hepatocellular carcinoma is unknown. In this article different aspects of aflatoxin are reviewed with emphasis on its relationship with HBV infection and with such neoplasia.